2020
DOI: 10.7189/jogh.10.020410
|View full text |Cite
|
Sign up to set email alerts
|

The role of smoke from cooking indoors over an open flame and parental smoking on the risk of cleft lip and palate: A case- control study in 7 low-resource countries

Abstract: Background Cleft is one of the most common birth defects globally and the lack of access to surgery means millions are living untreated. Smoke exposure from cooking occurs infrequently in developed countries but represents a high-proportion of smoke exposure in less-developed regions. We aimed to study if smoke exposure from cooking is associated with an increased risk in cleft, while accounting for other smoke sources. Methods We conducted a population-sampled case-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 43 publications
0
8
0
1
Order By: Relevance
“…Maternal exposure to numerous chemicals that are released into the air as a result of the incomplete combustion of tobacco and other organic compounds such as cooking and heating fuels have been shown to cause cracks; these substances include polycyclic aromatic hydrocarbons (PAHs), carbon monoxide (CO) and heavy metals [ 133 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maternal exposure to numerous chemicals that are released into the air as a result of the incomplete combustion of tobacco and other organic compounds such as cooking and heating fuels have been shown to cause cracks; these substances include polycyclic aromatic hydrocarbons (PAHs), carbon monoxide (CO) and heavy metals [ 133 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of open flames for cooking and heating, high density housing situations often with multi-generational occupancy, and lack of residential and industrial construction regulations are all risk factors that contribute to the high incidence of burn injury within Malawi, especially in pediatric and epileptic patients. In addition to preventing burns, providing safe alternatives to open fire cooking may help address other reconstructive issues as one recent study found that pregnant women exposed to cook smoke from open fire had higher risk of birthing children with congenital anomalies [ 55 ]. Suggested solutions in the literature include the use of public awareness campaigns for parents to encourage altered behaviors and instill safe practices around open fire cooking and heating to reduce the incidence of pediatric burns.…”
Section: Discussionmentioning
confidence: 99%
“…This holds true for environmental exposures as well, which may not have been studied due to negligible prevalence in high-resource countries. For example, while maternal smoking may be an important contributor to cleft risk in westernized populations, in low-resource countries where few women smoke, the primary source of exposure to smoke-related agents and therefore attributable risk of NSOFCs, may be from biomass cooking (Mbuyi-Musanzayi et al, 2018; Auslander et al, 2020).…”
Section: Discussionmentioning
confidence: 99%